A poética do desenho em terapia de casal - Borges, André Luiz de Biagi (2013)
Couple therapy, influenced by the discourse of social constructionism in its theorethical multiplicity, emphasizes the use of language as the builder of reality. However, it typically restricts its interest to the resources of verbal language, devoting little attention to other linguistic forms. Considering the possibility of contributing to this knowledge, we propose the inclusion of drawings as a language resource for therapeutic practices, increasing the understanding of the use of the language in a responsive-relational joint action for construction of meanings. Thus, this study aims at understanding the relational processes of meaning co-construction through the creation of drawings, in the context of Couple Therapy, seeking, in a special way, to analyze the implications of the use of drawings in the construction of change narratives of oneself and the marriage relationship. The study was carried out by way of video recordings of the therapy sessions of three couples, in 10 weekly sessions in a social clinic context. The analysis of the data, based on the constructionist version of social poetics, included transcripts of all sessions, followed by readings that allowed for the identification of different uses of the drawings. From the analysis of the drawings produced by the three couples, we identified drawing as a creative resource to: (a) facilitate conversation hampered by tension, (b) signal focus and selection of oscillatory conversation, (c) explore what has not yet been said in conversation, (d) strengthen the descriptions and narratives created in conversation and (e) summarize the assessment process. The detailed analysis of the therapeutic process of one of the couples, which presented a greater variation of elements referring to individual and marital aspects, showed that the practice of drawing in marital therapy creates participatory contexts in which spouses could feel safe to engage in the creative process, with inventive possibilities of one coming to be desirable and satisfying. In this way, the drawings became a propitiatory resource in bringing life to the use of the word, as well as promoting other forms of speech, freed from the captivity of the usual modes, normalized within human relationships. In couple therapy, drawings are possible as a new part of our language which incorporated with the usual and within the same, allows for the learning of new gestures and the production of new meanings.